REKRUTMEN CALON ANGGOTA LEGISLATIF OLEH PARTAI POLITIK (KAJIAN TENTANG KUALITAS DAN PROFESIONALITAS ANGGOTA LEGISLATIF DI PARLEMEN) - Firdaus, Firdaus; Rudiadi, Rudiadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
AbstractRecruitment of candidates for legislative members is carried out by Political Parties based on the Articles of Association (AD) and Bylaws (ART), and must pay attention to educational background, abilities and knowledge of politics, government and state administration, not just paying attention to candidates who have large capital, so they are immediately accepted as candidates. This is a habit that must be corrected and changed by the political parties participating in the election, so that the elected candidates can truly carry out the people's mandate and not disappoint the people. In addition, the quality and professionalism of elected legislative members is largely determined by the mechanisms and recruitment carried out by political parties, as well as the implementation of elections in accordance with their principles, namely direct, general, free, secret, honest and fair, as well as with the principles of proper implementation. independent, open, proportional, professional, effective and efficient. If this is done as well as possible and in accordance with applicable regulations, it is hoped that it will produce legislative members of quality and professionalism, but if on the contrary, the elected legislative candidate will not produce performance in accordance with their main duties and expectations of the people who elect them, so that the contribution of the selected candidate does not have a significant impact on the progress of society, nation and state, and overall will experience losses for five years.Keywords: Recruitment of Candidates for Legislative Members, Political Parties, General Election AbstrakRekrutmen calon anggota legislatif yang dilakukan oleh Partai Politik berdasarkan Anggaran Dasar (AD) dan Anggaran Rumah Tangga (ART), dan harus memperhatikan latar belakang pendidikan, kemampuan, dan pengetahuan tentang politik, pemerintahan, dan ketatanegaraan, tidak semata-mata hanya memperhatikan calon yang mempunyai modal besar, sehingga langsung saja diterima sebagai calon. Hal ini merupakan kebiasaan yang harus diperbaiki dan dirubah oleh partai politik peserta pemilu, agar calon yang terpilih memang benar-benar dapat mengemban amanah rakyat dan tidak mengecewakan rakyat. Di samping itu, kualitas dan profesionalitas anggota legislatif yang terpilih sangat ditentukan oleh mekanisme dan rekrutmen yang dilakukan oleh partai politik, serta penyelenggaraan pemilu yang sesuai dengan asasnya, yakni langsung, umum, bebas, rahasia, jujur, dan adil, serta dengan prinsip penyelenggaraan yang mandiri, terbuka, proporsional, professional, efektif dan efisien. Apabila hal ini dilakukan dengan sebaik-baiknya dan sesuai dengan ketentuan yang berlaku, maka diharapkan akan menghasilkan anggota legislatif yang berkualitas dan profesionalitas, tetapi apabila sebaliknya maka calon anggota legislatif yang terpilih tidak akan menghasilkan kinerja yang sesuai dengan tupoksinya dan harapan masyarakat yang memilihnya, sehingga kontribusi dari calon terpilih tidak membawa dampak yang signifikan bagi kemajuan masyarakat, bangsa dan negara, dan secara keseluruhan akan mengalami kerugian selama lima tahun.Kata Kunci: Rekrutmen Calon Anggota Legislatif, Partai Politik, Pemilihan Umum